Um modelo dinâmico de aprendizagem em grupo - Lizeo, Elaine (2004)
The objective of this thesis is to study the factors that influence the quality of group learning and group effectiveness. This study regards work groups as complex social systems and suggests that the explanation of the quality of learning and the effectiveness of a group lies in the interrelations of structural, cognitive and interpersonal factors. This study emphasizes the importance of applying systems thinking to understand complex systems and builds a conceptual system dynamics model, based on literature review – learning at the individual, group and organizational levels, effectiveness, and group dynamics – and on three case studies. At the end of the thesis, a generic, qualitative model is offered to whom is interested in a systems analysis of the complexities that encompass the learning process and effectiveness of work groups.